Hubungan antara Kecemasan Menghadapi Pertandingan dengan Motivasi Berprestasi pada Atlet Anggar di DKI Jakarta - Dian Anggraini Kusumajati (Humaniora, 2011)
Abundant anxiety in athletes causes emotional disorder so their attention focus is torn at the moment. The purpose of this research is to find out the relationship between anxiety in facing the match and achivementcentered motivation of fence athletes in Jakarta. The research population is 60 fencers in Jakarta that fulfill the characteristics using random sampling technique and used-try out. The instrument is using Likert scale, including anxiety questionnaire in facing matches for 66 items and achivement motivation questionnaire in 48 items. The data analysis is using SPSS 7.5. The correlation technique of Product Moment Karl Pearson is for validity test, meanwhile Alpha Cronbach technique for reliability analysis. The result of this research is that there is significant relationship between anxiety facing matches and motivation of fencers in Jakarta. However, the relationship is negative, which means the more anxiety in facing matches, the less achievement motivation ofthe fencers; and vice versa.